Supraparticles on beads for supported catalytically active liquid metal solutions - the SCALMS suprabead concept - Zimmermann, Thomas; Madubuko, Nnamdi; Groppe, Philipp; Raczka, Theodor; Dünninger, Nils; Taccardi, Nicola; Carl, Simon; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Wasserscheid, Peter; Mandel, Karl; Haumann, Marco; et al. (Materials Horizons, 2023)
A novel GaPt-based supported catalytically active liquid metal solution (SCALMS) material is developed by exploiting the suprabead concept: Supraparticles, i.e. micrometer-sized particles composed of nanoparticles assembled by spray-drying, are bonded to millimeter-sized beads. The suprabeads combine macroscale size with catalytic properties of nanoscale GaPt particles entrapped in their silica framework.
Created from Fastlane, Scopus look-up